Dielectric permittivity of (Ag₃AsS₃)x(As₂S₃)₁₋x superionic glasses and composites - Studenyak, I.P.; Neimet, Yu.Yu.; Orliukas, A.F.; Kežionis, A.; Kazakevičius, E.; Šalkus, T. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Complex dielectric permittivity of (Ag₃AsS₃)x(As₂S₃)₁₋x (x = 0.3−0.9)
superionic glasses and composites at 300 K were studied. A decrease of the real part of
dielectric permittivity with frequency by almost five orders of magnitude as well as one
dispersion region in glasses and two dispersion regions in composites, which is reflected
in the dielectric loss spectra, were observed. Frequency dependences of dielectric
permittivity within the range from 10 Hz to 3x109 Hz were analyzed in the framework of
the Cole-Cole model. Compositional behaviour of Cole-Cole parameters in
(Ag₃AsS₃)x(As₂S₃)₁₋x (x = 0.3−0.9) superionic glasses and composites was studied. The
most substantial changes were observed with the transition from (Ag₃AsS₃)₀.₄(As₂S₃)₀.₆
glass to (Ag₃AsS₃)₀.₅(As₂S₃)₀.₅ composite and from (Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ composite to
(Ag₃AsS₃)₀.₈(As₂S₃)₀.₂ composite.